The moderating role of previous venture experience on breadth of learning and innovation and the impacts on SME performance. Issue 2 (23rd November 2021) - Sinha, Kanhaiya K.; Saunders, Chad; Raby, Simon; Dewald, Jim
Abstract : Purpose: The purpose of this paper is to investigate the moderating role of previous venture experience on the relationship between learning breadth and innovation breadth, defined as the range of innovation types within a firm, and the impacts on SME performance. Design/methodology/approach: A theoretical model was developed, and hypotheses were tested using step-wise multivariate regressions on survey data from 509 North American SME respondents. Findings: The results demonstrate that the previous venture experience of a firm's top management plays a key role in enhancing the innovation breadth for a given level of learning breadth. There is a curvilinear relationship between innovation breadth and learning breadth, and increases in innovation breadth lead to increases in firm performance. Practical implications: The results indicate that organizations seeking higher performance returns by expanding their breadth of innovations need parallel attention on higher learning breadth in order to adequately capture the value from this broader set of innovations. Originality/value: The paper contextualizes learning and innovation in the SMEs and argues that the consideration of diversity (breadth) of learning and innovation can help us understand their performance implications across industries. It also extends the effect of previous venture experience (PVE) of the leadership team in explaining performance. Beyond their ability to address external factors, PVE has a moderating effect on the relationship between learning and innovation breadth across the organization. Previous venture experience serves as both a guide and catalyst for investments in learning activities that lead to a broader range of innovation activities across the firm.